Anchoring Principles of a New Energy-Absorbing Expandable Rock Bolt - WEN, Zhijie; JIANG, Yujing; HAN, Zuozhen; YANG, Sitong; WANG, Xiao (Engineering Transactions, 2016)
The greater the mine, the harder stability control will be. And the conventional rock bolts do not adapt well to the severe rock stress conditions. An ideal bolt having a high resistance and large deformation should be developed. Based on the test results and theoretical study, this paper proposes an energy-absorbing expandable rock bolt, which consists of the bar, sleeve, bolt plate, nut, and bolt end. The anchoring mechanism and its efficiency were systematically analysed in the laboratory and in practice: the anchoring mechanism and supporting density, especially the quantitative relationship, were deduced under the Energy Balance Theory, that is, E_B=12 n · F_0·(u_0+2Δ u). As compared with the conventional bolt and large deformation bolts, the new type of bolt could provide a larger constant resistance, even in the soft rock roadway with large squeezing deformation, the pulling force can be achieved by F=A · σ · f_2, it mainly being generated by a normal stress acting on the pore surface. These characteristics are helpful in making the supported roadway safe. The amount of released energy during the large deforming process of the surrounding rock is expressed through conservation of energy, which can provide reference to the quantitative calculation of the bolt supporting system